Thrombin-induced Hyperactivity of Platelets of Young Stroke Patients - Vanschoonbeek, Kristof; Feijge, Marion A. H.; Keuren, Jeffrey F. W.; Hemker, H. Coenraad; Lodder, Jan J.; Hamulyák, Karly; van Pampus, Elisabeth C. M.; Heemskerk, Johan W. M. (Thrombosis and Haemostasis, 2002)
Activated platelets are implicated in the development of premature arterial vascular diseases, in particular ischemic stroke. Since elevated cytosolic [Ca2+]i is an integrative marker of platelet activation, we determined the generation of Ca2+ signal in stimulated platelets from 26 young patients recuperating from stroke, 20 patients with symptomatic peripheral arterial disease, and 56 healthy volunteers. Even in the presence of aspirin, the platelets from various individuals showed highly different thrombin-induced Ca2+ responses. On average, the thrombin-induced Ca2+ response was increased for platelets from either patient group in comparison to the controls (P <0.04). Relatively more stroke patients had high-responsive platelets (27%, 7/26) than patients with peripheral arterial disease (10%, 2/20) or healthy subjects (4%, 2/56). The average prothrombinase activities of platelets from patients and controls were similar, but 3 out of 6 patients with increased thrombin-induced Ca2+ responses also exhibited high prothrombinase activity. In a follow-up study, the subject-dependent thrombin-induced Ca2+ response was found to correlate strongly with the platelet response to protease-activated receptor 1 (PAR1) agonist (r = 0.91), but was not linked to the PlA1/2 polymorphism. It is concluded that a significant part of young patients with stroke have platelets with hyperactivity toward thrombin, which is not normalised by aspirin treatment. Furthermore, the subject-dependent variation in thrombin-induced signalling is likely to involve PAR1-mediated platelet activation.
Keywords: Aspirin; calcium; ischemic stroke; platelets; thrombin receptors